Host genotype and infection status interact to shape microbiomes in Daphnia magna - Amruta Rajarajan; Ellen Decaestecker; Lore Bulteel; Jean-Claude Walser; Piet Spaak; Justyna Wolinska (Parasitology)
Host–bacterial communities (microbiomes) are influenced by a wide range of factors including host genotype and parasite exposure. However, few studies disentangle temporal and host-genotype-specific variation in microbiome response to infection across several host tissues. We experimentally exposed the freshwater crustacean Daphnia magna to its fungal parasite Metschnikowia bicuspidata and characterized changes in host–bacterial communities associated with the parasite's development within the host. We used 16S rRNA gene sequencing to assess bacterial communities of the host (a) 24 h (‘initial parasite exposure’) and (b) 10 days (‘successful infection’) after exposure to a standard dose of M. bicuspidata spores, in host guts, body tissue (excluding guts) and whole individuals. We also investigated whether bacterial community responses to parasite exposure varied by host genotype.